Postoperative T1 tilt is a risk factor for postoperative distal adding-on in Lenke type 1 adolescent idiopathic scoliosis: A preliminary report. Issue 21 (22nd May 2020) - Sakai, Yusuke; Takenaka, Shota; Makino, Takahiro; Yoshikawa, Hideki; Kaito, Takashi
Abstract : Abstract: Retrospective comparable study. Postoperative loss of correction, which is referred to as the distal adding-on phenomenon, sometimes occurs during the postoperative course in Lenke type 1 adolescent idiopathic scoliosis (AIS). Selection of the lowest instrumented vertebra (LIV) has been reported to be one of the significant factors for preventing distal adding-on. However, proximal parameters, such as the Cobb angle of the proximal thoracic (PT) curve, radiographic shoulder height, and T1 tilt, were rarely described in previous reports. This study aimed to identify the risk factors for postoperative distal adding-on, including proximal radiographic parameters, in Lenke type 1 AIS. Preoperative and postoperative radiographs of 34 consecutive patients with Lenke type 1 curve who underwent selective thoracic fusion were analyzed. The patients were divided into an adding-on group and a no-adding-on group according to the presence of adding-on at a 2-year follow-up. The 2 groups were compared with regard to age at surgery, Lenke lumbar modifier, Risser grade, instrumentation type, and radiographic parameters. Distal adding-on was noted in 10 patients (29%). The adding-on group had significant variables including preoperative larger PT Cobb angle ( P  = .002), larger main thoracic (MT) flexibility ( P  = .006), smaller thoracolumbar (TL) Cobb angle ( P  = .012), larger LIV shift ( P  < .001), larger T1 tilt ( P  = .001), postoperative larger PT Cobb angle ( P  = .012), smaller MT Cobb angle ( P  = .016), smaller TL Cobb angle ( P  < .001), larger PT–MT mismatch ( P  < .001), larger LIV shift ( P  = .026), and larger T1 tilt ( P  = .006) when compared with the findings in the no-adding-on group. Postoperative T1 tilt was significantly correlated with PT–MT mismatch. Our findings suggest that not only the LIV but also proximal parameters, including T1 tilt and PT–MT mismatch, are associated with postoperative distal adding-on in Lenke type 1 AIS. Strategies to reduce postoperative T1 tilt and PT–MT mismatch are required to prevent distal adding-on.